Boundary Element Calculations for Normal Contact of Soft Materials With Tensed Surface Membrane - Yuan, Weike; Wang, Gangfeng (Frontiers in Mechanical Engineering, 2020)
This work considers the non-adhesive frictionless contact problem of soft materials with surface being tensed by equi-biaxial tension. The boundary element method based on Fast Fourier Transform and conjugate gradient algorithm is extended to deal with this problem. By comparing with existing analytical solutions for the axisymmetric contact between a rigid parabolic indenter and an elastic half space with constant membrane/surface tension, our numerical simulations are validated having great accuracy and efficiency. Then, with this numerical tool, we further calculate the contact responses of a soft substrate indented by a smooth indenter with general quadric profile and a rough indenter with self-affine fractal surface, respectively. Some nontrivial contact behavior resulted from the presence of membrane tension are demonstrated and discussed.